Kształtowanie kompetencji społecznych młodzieży w programach UE. Teoria i praktyka = Shaping social competencies of the youth in EU programmes.Theory and practice - Sińczuch, Marcin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article concerns social competencies of the youth. The first part deals with the way the competencies of young people are present in the theory of sociology, in particular how defining the competencies is connected with the dominant contexts in given periods. The author presents different sets of key social competencies related to socialization in a group, nonconformity, adjustment to the late-capitalist market and functioning in a state of uncertainty and risk.
Keywords: youth; socialization; social competences; EU youth policy; "The youthin action" programme; młodzież; socjalizacja; kompetencje społeczne; program "Młodzież w działaniu"